Fasilitas dan Pelayanan sebagai Faktor Determinan Kepuasan Masyarakat: Studi Empiris di Kelurahan Gaharu,Kecamatan Medan Timur Kota Medan: Facilities and Services as Determinants of Public Satisfaction An Empirical Study in Gaharu Sub-regency, East Medan Regency, Medan City - Zhaki, Ahmad; syauqi, teuku; Nasution, Umar Hamdan (Puslatbang KHAN, 2025)
This study aims to analyze the effect of facilities and employee services on community satisfaction at the Gaharu Sub-regency Office, East Medan Regency, Medan City. The research method uses a quantitative approach with a sample of 100 people. The data in this study used multiple linear analysis. The results showed that facilities and employee services have a positive and significant influence on community satisfaction at the Gaharu sub-regency Office. With hypothesis testing, the facility variable (X1) has a thitung value of 0.893> ttable 0.2050, or a Sig value of 0.013 <0.05. This means that the facility factor at the Gaharu sub-regency Office significantly affects the level of community satisfaction. Services variable (X2) has a thitung value of 2.261> ttable 0.2050, or a Sig value of 0.003 <0.05. This indicates that the level of employee service at the Gaharu sub-regency Office significantly affects the level of community satisfaction. Sig. value for the effect of facilities (X1) and services (X2) on public satisfaction (Y) is 0.000 <0.05 or by looking at the Fhitung value is 12.124. Based on these findings, it is recommended that relevant agencies improve physical and technological facilities, provide training and development to employees to improve skills and responsibilities, and intensify the integration of technology in public services.